Emaranhamento em moléculas de pontos quânticos semicondutores - Oliveira, Patrícia Aparecida Almeida de (2019)
In this thesis, we will analyze quantum entanglement phenomena in systems composed of quantum molecules, considering two different models. In the first, N molecules, each with a single excess electron, interact via Coulomb coupling. This interaction is restricted to the first neighbors. In the second system, electrons from distinct molecules interact with each other through the electron-phonon coupling. Considering the N-molecule system, we broadened our studies started in the master’s degree to verify the characteristics of the energy spectrum and eigenstates for the molecule system. We focus on the scalability of the system and its effect on entanglement, showing that some specific eigenstates are systematically associated with the maximally entangled GHZ states, regardless of the number of molecules. In the second part of the work, we explore the entanglement of both the electronic subsystem and the phonon subsystem, defining a new base composed of Bell’s electronic states associated with the excitation states in vibrational modes, which allows rewriting the Hamiltonian to the composite system. From this point of view, it is possible to determine a set of 4 ⊗ 4 matrix subspaces that elucidated the study of the entanglement behavior in both subsystems, allowing the determination of distinct sets of parameters effective in generating highly entangled states in the electronic subsystem and now in the phononic subsystem.